5R pseudo-rigid-body model for inflection beams in compliant mechanisms. (October 2017) - Yu, Yue-Qing; Zhu, Shun-Kun
Highlights: A 5R pseudo-rigid-body model (PRBM) is proposed for inflection beams in compliant mechanisms. The characteristic parameters of 5R PRBM are determined via optimization and linear regression. The advantage of 5R PRBM is shown through a comparison with elliptical integral solutions. This model can be used to predict both the tip locus and inflection position of flexural beams. Abstract: A 5R pseudo-rigid-body model (PRBM) is proposed for inflection beams in compliant mechanisms. This new model consists of six rigid links connected by five joints. Four joints with torsional spring are added at the joints to simulate the deflection and a free hinge without spring is used to present the inflection point of the flexural beam. An objective function is established according to relative angular displacement between the two rigid links jointed by the free hinge for finding the optimal characteristic parameters of the 5R PRBM. The spring stiffness coefficients of the 5R PRBM are obtained using a linear regression technique. Numerical examples are presented and the results are shown by comparing with elliptical integral solutions. This new pseudo-rigid-body model behaves as load independent and can be used to predict both the tip locus and inflection position of flexural beams.